AN EXAMINATION OF EMERGENCY SERVICES RESEARCH IN PUBLIC ADMINISTRATION - HENDERSON, ALEXANDER C.; CHARBONNEAU, ÉTIENNE (Public administration quarterly, 2016)
The scholarly field of public administration has long embraced emergency management as a distinct area of inquiry, producing a substantial body of both conceptual and empirical research. However, not all emergency incidents are alike. Larger-scale crises and disasters differ in substantial ways from more "routine" or "everyday" services. We examine and report on the latter, focusing on the conceptual and empirical treatment of routine emergency services in 19 US-based public administration journals from 1999 to 2013. This stock-taking article describes the service focus; the focal topic and purpose of the research; the conceptual or empirical orientation, the unit of analysis, sampling logic and sample size, and data collection sources and methods. Findings indicate that most articles focus on the policing and law enforcement as opposed to fire and emergency medical services. Research foci generally include mainstay topics like human resources, organizational behavior, management, and professionalism, though some focus on topics more specific to these services like community-citizen interactions. This body of existing research is largely exploratory in nature, and primarily uses quantitative data. Directions for future research and concluding comments are provided.